Filamentous temperature sensitive mutant Z: a putative target to combat antibacterial resistance. Issue 17 (11th April 2023) - Kifayat, Sumaiya; Yele, Vidyasrilekha; Ashames, Akram; Sigalapalli, Dilep Kumar; Bhandare, Richie R.; Shaik, Afzal B.; Nasipireddy, Venkatarathnam; Sanapalli, Bharat Kumar Reddy
Abstract : Different inhibitors (natural, synthetic and peptides) against FtsZ alongwith detection techniques to quantify the FtsZ-drug complex. Abstract : In the pre-antibiotic era, common bacterial infections accounted for high mortality and morbidity. Moreover, the discovery of penicillin in 1928 marked the beginning of an antibiotic revolution, and this antibiotic era witnessed the discovery of many novel antibiotics, a golden era. However, the misuse or overuse of these antibiotics, natural resistance that existed even before the antibiotics were discovered, genetic variations in bacteria, natural selection, and acquisition of resistance from one species to another consistently increased the resistance to the existing antibacterial targets. Antibacterial resistance (ABR) is now becoming an ever-increasing concern jeopardizing global health. Henceforth, there is an urgent unmet need to discover novel compounds to combat ABR, which act through untapped pathways/mechanisms. Filamentous Temperature Sensitive mutant Z (FtsZ) is one such unique target, a tubulin homolog involved in developing a cytoskeletal framework for the cytokinetic ring. Additionally, its pivotal role in bacterial cell division and the lack of homologous structural protein in mammals makes it a potential antibacterial target for developing novel molecules. Approximately 2176 X-crystal structures of FtsZ were available, which initiated the research efforts to develop novel antibacterial agents. The literature has reported several natural, semisynthetic, peptides, and synthetic molecules as FtsZ inhibitors. This review provides valuable insights into the basic crystal structure of FtsZ, its inhibitors, and their inhibitory activities. This review also describes the available in vitro detection and quantification methods of FtsZ-drug complexes and the various approaches for determining drugs targeting FtsZ polymerization.